2020
DOI: 10.1159/000505606
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Persons with Multiple Myeloma in Underprivileged Circumstances: Real-World Data from a Single Institution

Abstract: Background: The treatment of patients with multiple myeloma (MM) has evolved in recent years, and the disease-associated prognosis has improved substantially. This improvement has been driven largely by the approval of novel agents, many of which are expensive and not universally available. Less expensive but effective approaches would be of value globally. Patients and Methods: All consecutive MM patients diagnosed in the Centro de Hematología y Medicina Interna de Puebla after 1993 were included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The diminished aggressiveness of CLL in México may stem from several facts: (a) Most patients (80%) presented in this study in early stages of the disease (Rai stages 0-2); (b) 89% of patients were ZAP-70 negative, whereas in Caucasians the negativity of ZAP-70 is around 60% [12]; (c) There were no cases of T-CLL; (d) Genetic factors may be involved as has been shown in multiple myeloma [4,[9][10][11], and (e) Other unknown reasons.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The diminished aggressiveness of CLL in México may stem from several facts: (a) Most patients (80%) presented in this study in early stages of the disease (Rai stages 0-2); (b) 89% of patients were ZAP-70 negative, whereas in Caucasians the negativity of ZAP-70 is around 60% [12]; (c) There were no cases of T-CLL; (d) Genetic factors may be involved as has been shown in multiple myeloma [4,[9][10][11], and (e) Other unknown reasons.…”
Section: Discussionmentioning
confidence: 64%
“…As far as the age of the patients is concerned, the median age was found to be lower than that informed in Caucasian populations (65 versus 70 years) [8]. We have previously shown that multiple myeloma, in addition to being less frequent in Mexican mestizos, is also less aggressive [9,10]. In this study, despite the use of medications that were not especially expensive, we observed good patient outcomes in patients with newly diagnosed CLL, with an OS of more than 20 years (median not yet reached): these data suggest that the clinical course of CLL patients in México is less aggressive than in Caucasian populations, as it has been shown in multiple myeloma [9][10][11].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Jean Bernard, an icon in the world's hematology, presented in 1963 the concept of "geographic hematology" distinguishing two major branches; the so-called "ethnic hematology" that dealt with differences between populations and a second branch about environmental factors such as food habits, infections, and its implication with the hematological diseases referred as "environmental hematology" 4,7 . Along this line, we have analyzed the salient features of several hematological diseases, making comparisons with the features of some conditions in other populations 4 : we have shown that two B-cell malignancies, both CLL and multiple myeloma, are less frequent and less aggressive in México than in Caucasian populations 4,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Acta Haematologica, Murrieta-Alvarez et al [1] report on the results of plasma cell myeloma (PCM) therapy at an advanced cancer centre in Puebla Mexico where many anti-myeloma drugs, including dexamethasone, thalidomide, bortezomib, and lenalidomide, were available but many newer therapies such as pomalidomide, carfilzomib, xiazomib, and daratumu­mab were not. Moreover, not everyone had access to bor­tezomib and lenalidomide because the costs of these drugs are not covered by Mexico’s national health insurance.…”
mentioning
confidence: 99%